2021
DOI: 10.1007/s11357-021-00322-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and future avenues in understanding the role of adipose tissue cross talk in mediating skeletal muscle mass and function with ageing

Abstract: Sarcopenia, broadly defined as the age-related decline in skeletal muscle mass, quality, and function, is associated with chronic low-grade inflammation and an increased likelihood of adverse health outcomes. The regulation of skeletal muscle mass with ageing is complex and necessitates a delicate balance between muscle protein synthesis and degradation. The secretion and transfer of cytokines, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), both discretely and within extracellular vesicles, have emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 302 publications
(326 reference statements)
1
17
0
Order By: Relevance
“…Importantly, obesity is a risk factor for OA, but the relationship between obesity and OA may not simply be due to weight-related increased loading on the joint, since BMI is also associated with the development of OA in non-weight-bearing joints, such as the hands [3,4]. One group of proteins that provide a link between obesity and joint damage are the adipose-secreted cytokines (adipokines), which are known regulators of metabolism [5][6][7][8][9][10] and the inflammatory response [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, obesity is a risk factor for OA, but the relationship between obesity and OA may not simply be due to weight-related increased loading on the joint, since BMI is also associated with the development of OA in non-weight-bearing joints, such as the hands [3,4]. One group of proteins that provide a link between obesity and joint damage are the adipose-secreted cytokines (adipokines), which are known regulators of metabolism [5][6][7][8][9][10] and the inflammatory response [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge about developmental biology suggests the growth of skeletal muscle preceding that of AT; however, with age the growth speed of AT increases, while that of skeletal muscle decreases [ 50 ]. The relative proportion of these different tissues is regulated throughout life, and changes in their proportion at different developmental stages may affect relevant metabolic regulation, contributing the occurrence of disease.…”
Section: Adipose-derived Exosomes In Adipocyte–myocyte Crosstalkmentioning
confidence: 99%
“…Because of expanding capacity of adipocytes in animal tissues, ectopic intermuscular lipid deposition is frequently observed within the perimysium of skeletal muscles, which become disorganized and remodeled as adipocytes mature [ 96 ]. In vitro studies have suggested that perimuscular lipid deposition accelerates aging-induced muscle atrophy factor-related proteolysis and muscle senescence, and induces progressive loss of skeletal muscle mass and function [ 50 , 97 ]. Moreover, the lipid deposition in skeletal muscle can also induce a shift from type II fibers to a type I phenotype, leading to impaired muscle contractility of both type I and type II fibers, resulting in a dramatic decrease in muscle strength [ 98 ].…”
Section: Lipidsmentioning
confidence: 99%
“…Knowledge about tissue growth suggests prioritization or a competition for the growth of muscles compared to that of adipose tissue. Indeed, the growth of muscle precedes that of adipose tissue, and growth allometric analysis shows that the growth speed of adipose tissue increases with age, while that of muscle decreases [4]. The relative proportion of these different tissues is regulated throughout life, and the alteration of this ratio, either during the prenatal stage or after birth, impairs the control of body weight and fasting glycemia, and it can contribute to diabetes and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%